Frequency and Pattern of presentation of Oral Squamous Cell Carcinoma and its predisposing Factors in patients presented to Nishtar Institute of Dentistry - Tauseef Zahra, Zehra Jawa, Tehzeeb Zahra, Asif Nazeer, Hassan Raza, Uzma Batool (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the Frequency and Pattern of Presentation of Oral Squamous Cell Carcinoma and its Predisposing Factors in Patients Presented to Nishtar Institute of Dentistry. Study design: Cross sectional study. Place and Duration of Study: Study was conducted from Aug 2021 to Jan 2022 at Nishtar Institute of Dentistry. Methodology: A total of 100 patients were included. Patients aged between18-80 years males and females were included whom were presented with oral squamous cell carcinoma. Detailed history and biopsy was taken along with CT scan or MRI. Radiological findings and TNM staging was observed of the patients. Results: Among those 100 patients 60 (60%) males and 40 (40%) females, 67 % of patients were in between 41-60 years. 35 patients (35%) had a lesion in buccal mucosa, 24 patients (24%) were presented with eythroplakia while histopathological reports of 100 showed 44 patients (44%) had grade 1 (well differentiated squamous cell carcinoma. TNM showed 49 patients (49%) were placed in T1, 42 patients (42%) were in N2b and 13 patients (13%) had metastatic disease on presentation. Conclusion: Result shows that OSCC was present more in male population. Smoking was recorded as common risk factor. Buccal mucosa was common site of involvement followed by tongue. Ulceration was the frequent presenting feature while majority cases had moderately differentiated squamous cell carcinoma. Key words: oral squamous cell carcinoma, smoking, TNM